REPRODUCTION OF POLITICAL IDENTITY: ISLAM, ADAT AND THE POLITICS OF MUSLIM PUBLIC SPACE IN POST-NEW ORDER WEST SUMATRA - Zulfadli; Fajri, Mhd; Efirmasnyah, Rian (International Journal of Cultural and Social Science, 2026)
This study examines the reproduction of political identity in the construction of Muslim public spaces in West Sumatra. Studies that integrate policy aspects, visual symbols in public spaces, and social practices in the reproduction of political identities based on Islam and Adat remain relatively limited. Using a qualitative approach, data were collected through in-depth interviews, observations related to the visual symbols of Adat Basandi Syari’at, Syari’at Basandi Kitabullah (ABS-SBK), and analysis of a number of local regulations and policy documents. The research findings indicate that political identity in West Sumatra post-New Order is reproduced through regulations, regional development planning, and the creation of visual symbols and public discourse. Although this reproduction of identity has strengthened Minangkabau identity, it also has the potential to give rise to the politicization of identity and issues of inclusivity. Identities constructed through ABS-SBK practices and discourse tend to remain at the level of hegemonic jargon used for moral and political legitimization, while simultaneously being positioned as a “panacea” for responding to various forms of moral panic amid societal change. This study confirms that the reproduction of these identities tends to function symbolically and as slogans rather than substantively.